Modality and terminology changes for behavioral health service delivery during the COVID-19 pandemic: a systematic review - Elliott, Kimberly S.; Nabulsi, Eman H.; Sims-Rhodes, Nicholas; Dubre, Vandy; Barena, Emily; Yuen, Nelly; Morris, Michael; Sass, Sarah M.; Kennedy, Bridget; Singh, Karan P. (Frontiers in Psychiatry, 2024)
The COVID-19 pandemic prompted healthcare professionals to implement service delivery adaptations to remain in compliance with safety regulations. Though many adaptations in service delivery were reported throughout the literature, a wide variety of terminology and definitions were used. To address this, we conducted a PRISMA review to identify service delivery adaptations across healthcare systems in the United States from March 2020 to May 2022 and to identify variations in terminology used to describe these adaptations. We identified 445 initial articles for our review across eight databases using predetermined keywords. Using a two-round screening process, authors used a team approach to identify the most appropriate articles for this review. A total of 64 articles were examined. Our results suggested that a total of fourteen different terms were used to describe service modality changes, with the most frequent term being telehealth (63%). Each term found in our review and the frequency of use across identified articles is described in detail. Implications of this review such as understanding modality changes during the COVID-19 pandemic and beyond are discussed. Our findings illustrate the importance of standardizing terminology to enhance communication and understanding among professionals.